The Study Of Moral Values And Education On The Novel “Sukuh, Misteri Portal Kuno Di Gunung Lawu” The Work Of Rizki Ridyasmara And Its Relevance As A Reading Material In Sma Negeri 19 Medan - sunarti; Teguh Trianton (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study aims to determine the moral and educational values in the novel “Sukuh, Misteri Portal Kuno Di Gunung Lawu” by Rizki Ridyasmara and its relevance as reading material at SMA Negeri 19 Medan. The method used in this research is descriptive method. The research data is in the form of sentences that are described to explain moral values and educational values in the novel “Sukuh, Misteri Portal Kuno Di Gunung Lawu”. There are 20 moral values contained in this novel which are divided into moral values related to responsibility, humility, truth, attitude, never give up, and honesty. And there are 52 educational values which are divided into educational values related to curiosity, discipline, hard work, creative, democratic, and curiosity. The novel “Sukuh, Misteri Portal Kuno Di Gunung Lawu” by Rizki Ridyasmara is very relevant to be used as reading material, this is because the story in the novel “Sukuh, Misteri Portal Kuno Di Gunung Lawu” by Rizki Ridyasmara contains many moral and educational messages. This novel also contains many insights that are very much related to the country of Indonesia / the Archipelago. Reading this novel adds students' insight into knowing the natural heritage and wealth that exists in Indonesia and this novel is a novel with a historical genre where students really need novels with that genre to be used as reading material.